Tradisi Lawang Sakepeng Persyaratan Pernikahan Pada Suku Dayak Ngaju di Kecamatan Jekan Raya Kota Palangka Raya Kalimantan Tengah - Ahmad Kasbil Mubarak; Effendi, Rusdi; Mardiani, Fitri (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The purpose of this study is to provide a comprehensive description of the Lawang Sakepeng tradition in terms of marriage requirements. The method in this research uses qualitative with descriptive research type. Data were obtained through direct observation to the research location. Then, interviews with informants and people who have knowledge about the Lawang Sakepeng tradition. In addition, relevant documents and equipment used in carrying out Lawang Sakepeng. The results of the study show that the Lawang Sakepeng tradition plays an important role in determining the success of marriage by ensuring agreement and consent between the two parties and their families. This tradition is not only a formal ceremony, but also a moment to strengthen social and cultural relations within the Ngaju Dayak community.